Incidence of Lymph Node Metastases in Apparent Early-Stage Low-Grade Epithelial Ovarian Cancer: A Comprehensive Review. Issue 8 (October 2016) - Lago, Victor; Minig, Lucas; Fotopoulou, Christina
Abstract : Objectives: This study aimed to determine the incidence of lymph node (LN) metastases in presumed stage I-II low-grade epithelial ovarian cancer (EOC). Methods: Eligible studies were identified from MEDLINE and EMBASE (time frame, 2015–1975), that analyzed patients with clinical or radiologic presumed early-stage EOC who underwent a complete pelvic and para-aortic lymphadenectomy as part of their surgical staging. The number and site of dissected and involved LNs and the correlation with overall outcome are analyzed. The term low grade and also the older term well differentiated were used. Results: Thirteen of 978 identified studies were selected, and 13 of 75 studies were identified as eligible. A total of 1403 patients were analyzed in these 13 retrospective studies. The final International Federation of Gynecology and Obstetrics staging after completed surgical staging was I to II in 912 patients (65%). A total of 338 patients (24%) had grade 1 tumors whereas 473 patients (34%) had grade 2, and 502 patients (36%) had grade 3 tumors. Systematic lymphadenectomy was performed in 1159 patients (83%), whereof 1142 (82%) were pelvic and para-aortic LN dissections. In 185 patients (13%), an upstaging from an apparent clinical stage I-II to IIIC occurred because of LN involvement: 64 (35%) of the patients had only pelvic LNs metastases, 69 (37%) had only para-aortic LNs metastasis, and 51 (28%) had both a pelvic and para-aortic LN involvement. When analyzing only the patients with low-grade (grade 1 as the old classification) presumed early-stage disease (n = 273), only 8 patients (2.9%; range, 0–6.2) were identified with LNs metastases present. Conclusions: The incidence of occult LN metastases in apparent early-stage low-grade EOC is 2.9% in a metaanalysis of retrospective studies. Future larger-scale prospectively assessed studies with established surgical quality of the LN dissection are warranted to establish the true incidence of LN metastasis in presumed early low-grade disease.